2010
DOI: 10.1074/jbc.m109.044057
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal Hydrolase-L1 Protects Cystic Fibrosis Transmembrane Conductance Regulator from Early Stages of Proteasomal Degradation

Abstract: ⌬F508 cystic fibrosis transmembrane conductance regulator (CFTR) degradation involves ubiquitin modification and efficient proteasomal targeting of the nascent misfolded protein.We show that a deubiquitinating enzyme, ubiquitin C-terminal hydrolase-L1 (UCH-L1), is highly expressed in cystic fibrosis (CF) airway epithelial cells in vitro and in vivo. We hypothesized that the elevation in UCH-L1 in CF cells represents a cellular adaptation to counterbalance excessive proteasomal degradation. The bronchial epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…It is well known that F508del-CFTR protein degradation involves Ubiquitin modification. It was previoulsy shown that the de-ubiquitinating enzyme, Ubiquitin C-terminal hydrolase-L1 (UCH-L1), is highly expressed in CF airway epithelial cells and that there is a positive correlation between UCH-L1 expression and steady state levels of Wt-CFTR protein and F508del-CFTR [101]. Although it is not sufficient to rescue F508del-CFTR, the effect of UCH-L1 upon CFTR processing shows its potential roles in CF.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that F508del-CFTR protein degradation involves Ubiquitin modification. It was previoulsy shown that the de-ubiquitinating enzyme, Ubiquitin C-terminal hydrolase-L1 (UCH-L1), is highly expressed in CF airway epithelial cells and that there is a positive correlation between UCH-L1 expression and steady state levels of Wt-CFTR protein and F508del-CFTR [101]. Although it is not sufficient to rescue F508del-CFTR, the effect of UCH-L1 upon CFTR processing shows its potential roles in CF.…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas the J-domain protein DNAJB12 facilitates Hsc70 and Rma1-dependent ubiquitination of the non-native N-terminus cotranslationally [5355], CHIP (C-terminal Hsc70 interacting protein) preferentially recognizes the misfolded full-length CFTR. Gp78, an E4 ER Ub ligase [55], assists in poly-Ub chain extension, whereas UCH-L1 (ubiquitin C-terminal hydrolyse-L1) and Usp19 (ubiquitin specific protease 19) stabilize the ΔF508 CFTR nascent chain by catalyzing Ub cleavage [56, 57]. The cytosolic Nedd4-2 and Fbs1 E3 ligases have also been implicated in the ERAD of ΔF508 CFTR [58, 59].…”
Section: Membrane Trafficking and Functional Defects Of δF508 Cftrmentioning
confidence: 99%
“…ERAD is the key protective mechanism to maintain ER protein homeostasis in case of accumulation of misfolded proteins in the ER. Indeed, more than 99% of dF508CFTR protein can be degraded by ERAD, while only 25% of wild-type CFTR is degraded by the same pathway [23]. However, as shown in this study, human tracheal cells stably expressing the misfolded CFTR protein, dF508CFTR, exhibited significantly increased sumoylation of ATF6, a major transcriptional activator of ERAD program.…”
Section: Discussionmentioning
confidence: 62%